2014
DOI: 10.2478/10004-1254-65-2014-2546
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline disinfection of urban wastewater and landfill leachate by wood fly ash

Abstract: Wood fly ash is an industrial by-product of the combustion of different wood materials and is mostly disposed of as waste on landfills. In our preliminary experiments, wood ash exhibited antibacterial activity against urban wastewater bacteria and we focused on wood fly ash as a potential substrate for wastewater disinfection. The addition of ash at a concentration of 10 g L -1 (1 %) caused an instant increase of pH in urban wastewater and landfill leachate. High pH (10.1-12.7) inactivated bacterial population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Statistical analysis showed that the CRB37 and CRB42 counts correlated positively (p < 0.05) with each other and the He counts (Table 3) but showed no correlation (p > 0.05) with the Ie counts, pH, and water content in soil. The pH correlated positively with Ie (p < 0.05), as this type of bacteria better adapts to high pH (Meckes and Rhodes 2004;Ivankovic et al 2014). This finding also suggests that Ie, even though it is the usual indicator of anthropogenic influence, should not be considered as indicator of CRB presence in soil.…”
Section: Crb In Soilmentioning
confidence: 92%
“…Statistical analysis showed that the CRB37 and CRB42 counts correlated positively (p < 0.05) with each other and the He counts (Table 3) but showed no correlation (p > 0.05) with the Ie counts, pH, and water content in soil. The pH correlated positively with Ie (p < 0.05), as this type of bacteria better adapts to high pH (Meckes and Rhodes 2004;Ivankovic et al 2014). This finding also suggests that Ie, even though it is the usual indicator of anthropogenic influence, should not be considered as indicator of CRB presence in soil.…”
Section: Crb In Soilmentioning
confidence: 92%
“…This behavior could be attributed to several reasons. First, most bacteria can live and multiply within pH 5–8, while the bacteria growing at pH above 10 are very few [ 43 ]. Therefore, with this explanation, it is reasonable to think that the geopolymer can create hostile bacterial growth environments.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the concrete tile (CEM II) in which moss growth occurred, none of the geopolymeric tiles with (GP30%WA) and without filler (GP) did this growth. Geopolymeric material and wood ash, having a basic pH, may create a hostile environment for the formation of the bacterial layer [ 43 ]. It is known that the bacterial layer is responsible for the engraftment of the spores [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Complete inactivation of E. coli, Salmonella enterica serovar typhymurium, and Porcine circovirus type 2 was achieved when removing phosphate from swine slurry at pH 10 using Ca(OH) 2 (Viancelli et al, 2015). The coliforms was also completely inactivated after 6 h of treatment using wood ash Frontiers in Environmental Science frontiersin.org to remove phosphate from urban wastewater and landfill leachate at pH of 10.1-12.7 (Ivanković et al, 2014). In addition, the optimal pH in ranges of 10-11 for the precipitation of struvite-K (Xu et al, 2011;Xu et al, 2012;Xu K. et al, 2015) may also improve the pathogens inactivation in the liquid fraction despite this has not been reported.…”
Section: Chemical Precipitation To Obtain Solid Productsmentioning
confidence: 99%